Synthesis and Potentiometric Analysis of Organophosphorus Metal Complexones and Complexonates Based on 2-Aminothiazole Derivatives - Sal’keeva, L.K.; Shibaeva, A.K.; Taishibekova, E.K.; Nurmaganbetova, M.T.; Minaeva, E.V.; Sal’keeva, A.K. (Springer, 2011)
Abstract—Synthesis conditions of 4-phenyl-2-amidothiazolyl acetate and 2-thiourido-4-diethylphosphothiazole were developed, and the complexation capacity of these compounds in formation of mixed-ligand complexes was studied. The optimal conditions and thermodynamic parameters of the complexation process were determined. The potentiometric method was used to fi nd thermodynamic parameters of the reactions of mixed-ligand complexation with copper(II) and lead(II) ions, the composition of the complexes being formed on the basis of 4-phenyl-2-aminothiazole and its phosphorylated derivatives was determined.
Keywords: Synthesis; Potentiometric Analysis; Organophosphorus Metal; Complexones